Students' Learning Obstacles in Relational Thinking on Arithmetic, Algebra, and Linear Equations in One Variable - Lisda Fitriana Masitoh; Sufyani Prabawanto; Darhim Darhim; Al Jurpri (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Various studies on relational thinking have been conducted, but none have explicitly examined studentsâ€™ learning obstacles from the ontogenetic, epistemological, and didactical perspectives. This study aims to identify and describe studentsâ€™ learning obstacles in relational thinking within arithmetic, algebra, and linear equations in one variable. This study employs a qualitative approach guided by Miles and Hubermanâ€™s framework, which involves data collection, data reduction, data display, and drawing and verifying conclusions. The study used tests and interviews to gather information. Data were collected in August 2023 from 32 students of 8th grade at SMPN 17 Tangerang Selatan. Analysis revealed that students encountered ontogenetic, didactical, and epistemological obstacles when solving mathematics problems requiring relational thinking. The ontogenetic obstacle manifested as a lack of confidence in their own mathematical abilities. The didactical obstacle arose from the use of instructional materials and learning designs that did not facilitate development of relational thinking ability. The epistemological obstacle was evident in studentsâ€™ failure to understand arithmetic and algebraic operation rules, inability to construct mathematical models from everyday situations, and misinterpretation of the equals sign (â€œ=â€) as an operational command rather than a symbol of equality. Teachers therefore require additional learning resources to reinforce studentsâ€™ understanding of the concept of equality. Future research should focus on developing and evaluating instructional designs specifically aimed at enhancing studentsâ€™ relational thinking ability.